Oxygen mass transfer rate in a pressurized lab-scale stirred bioreactor - Lopes, Marlene (2013)
Oxygen mass transfer from air to the liquid phase in bioreactors with aerobic cultures has long been a serious impairment to the productivity of various bioprocesses. An increase of the oxygen mass transfer rate (OTR) can be the key to overcome oxygen limitation. The influence of higher air pressure on OTR was measured and a significantly enhanced OTR could be obtained. The oxygen volumetric mass transfer coefficient (kLa) was described by a function of the air pressure in a stirred lab-scale pressurized bioreactor. The correlation obtained proved that kLa slightly decreased with higher air pressure, following a power function.